J.S. Mill, W. Roscher and D.H. Robertson: The early history of the monetary misperceptions hypothesis - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2021)
Around 50 years ago, Edmund Phelps and Robert Lucas proposed an answer to the question why changes in aggregate nominal spending bring about output and employment effects, instead of purely proportional variations in prices. The Phelps-Lucas monetary misperception hypothesis asserted that imperfect information about the state of the economy may cause sluggish price or wage adjustment to emerge as reactions to monetary shocks in an otherwise perfectly flexible prices economy. The present paper documents how J.S. Mill, W. Roscher and D.H. Robertson addressed that issue in their respective notions of "general delusion", "generally prevailing error" and "monetary misapprehension", formulated between mid 19th and early 20th centuries. It also discusses how their contributions were not generally acknowledged until after Phelps and Lucas.
Keywords: B3; E3; 330; Monetary misperceptions; Mill; Roscher; Robertson; misinformation